2006
DOI: 10.1111/j.1740-0929.2006.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soluble glass bolus administration on the blood selenium concentration in grazing Philippine goats under backyard conditions

Abstract: The present study was conducted to determine the effects of selenium (Se) soluble glass bolus (SGB) on blood Se concentrations of mixed‐bred (native × Anglo Nubian) pregnant does weighing between 15 and 52 kg and grazing on natural pastures in the Philippines. The control group, consisting of 28 does, was not administered with SGB, while 23 does were administered with SGB every 6 months for a period of 12 months. Forage and blood samples in both groups were collected every 2 months. Their Se, sulfur, calcium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Although Se concentrations in group Se-Y exceeded 200 μg/l, the animals showed no signs of toxicity. Similarly to our results, other authors did not observe toxicity in goats with Se concentrations of above 200 μg/l (Hayashida et al 2006;Pechova et al 2008). The activity of glutathione peroxidase in blood strongly correlated with Se concentration in whole blood.…”
Section: Discussionsupporting
confidence: 91%
“…Although Se concentrations in group Se-Y exceeded 200 μg/l, the animals showed no signs of toxicity. Similarly to our results, other authors did not observe toxicity in goats with Se concentrations of above 200 μg/l (Hayashida et al 2006;Pechova et al 2008). The activity of glutathione peroxidase in blood strongly correlated with Se concentration in whole blood.…”
Section: Discussionsupporting
confidence: 91%
“…The highest concentration of Se in the blood in group S is also because of the incorporation of selenomethionine into hemoglobin and albumin instead of methionine. Any selenomethionine that is not immediately metabolized is incorporated into organs with high rates of protein synthesis such as the skeletal muscles, erythrocytes, pancreas, liver, kidney, stomach, and the gastrointestinal mucosa; the retention was similar to that observed with 35 S-methionine and 14 C-phenylalanine. This allows Se to be stored in the organism and reversibly released by normal metabolic processes, thus, offering an advantage over other Se compounds [12].…”
Section: Resultssupporting
confidence: 66%
“…We found no clinical symptoms of toxicity, and the blood examination showed no toxic effects of the administered selenium doses either. Like us, Hayashida et al [14] found concentration higher then 200 µg l −1 after administration of soluble glass Se bolus (130 µg per day) in Fig. 1 Selenium concentration in goat blood in individual groups (C control, S Se yeast, B Se proteinate, L Se lactate) at the beginning and at the end of monitored period.…”
Section: Resultsmentioning
confidence: 78%
“…The FEEDAP Panel reviewed those references; most of them were considered not suitable for this assessment since: (i) were performed in non‐ruminant species; (ii) the source of selenium was not sodium selenate; (iii) sodium selenate was not administered as a bolus; or (iv) no information was available on the source of selenium in the bolus. Only four papers could be considered partially relevant for this assessment (use of sodium selenate as a bolus in ruminant species): one was conducted in cattle (Sprinkle et al., ) and three in goat (Serra et al., ; Fujihara et al., ; Hayashida et al., – all from the same research group); however, none of them was a proper tolerance study, since the animals received an adequate dose of sodium selenate (together with other trace elements as cobalt and iodine) . All these studies were considered ‘field trials’ performed in ruminants fed on local pastures with the objective to provide a long‐term mineral supplementation to cover the physiological needs and improve productivity.…”
Section: Assessmentmentioning
confidence: 99%